2000
DOI: 10.1143/jjap.39.4616
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Uniform and Straight Nano-Pore Arrays on (001) InP Surfaces and Their Photoluminescence Characterizations

Abstract: Recently, <001>-oriented nanometer-sized pores (nano-pores) without side branches, unlike porous Si, have been realized by our group on (001) n-InP surfaces by means of electrochemical anodization in 1M HCl solution. However, they exhibit large structural nonuniformity including the presence of an irregular top layer, random pore positioning and wavy pore walls. In this study, attempts have been made to improve pore uniformity and to clarify their optical properties. Anodization in 1 M HCl+HNO3 solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 11 publications
3
50
1
Order By: Relevance
“…This behavior can be explained in terms of a quantum-size effect in the InP nanowalls, as similar to the template porous samples. 13 These results indicate that the cathodic decomposition process is very effective for the size tuning of InP nanoporous structures.…”
Section: H154mentioning
confidence: 85%
See 1 more Smart Citation
“…This behavior can be explained in terms of a quantum-size effect in the InP nanowalls, as similar to the template porous samples. 13 These results indicate that the cathodic decomposition process is very effective for the size tuning of InP nanoporous structures.…”
Section: H154mentioning
confidence: 85%
“…We have recently succeeded in the anodic formation of arrays of straight nanopores on n-InP͑001͒ substrates. [13][14][15] The straightness of pores in the depth direction has been dramatically improved using an HCl-based electrolyte containing a small amount of HNO 3 , resulting in the formation of a high-density array of InP nanowalls with a high aspect ratio. These kinds of unique nanostructures have not been obtainable by other methods.…”
mentioning
confidence: 99%
“…We have recently shown that <001>-oriented nanometer sized straight pores, penetrating deep into the semiconductor, can be produced by anodizing (001)-oriented n-type InP in the passive region in a suitable electrolyte [28][29][30]. Such capability of forming <001>-oriented pores seems to be useful for various applications, since (001)-oriented substrates are technologically more important than the (111)-oriented one.…”
Section: 1)formation Of Nanoporesmentioning
confidence: 99%
“…[15][16][17] The nanopores were laterally separated by InP nanowalls several tens of nanometers thick and formed in a straight vertical direction greater than several tens of micrometers. We previously reported that pore diameter and wall thickness can be controlled by adjusting the electrochemical anodic and cathodic conditions.…”
mentioning
confidence: 99%